Navigating stormy waters: 10 years of operation of the European Union Regulatory Network Incident Management Plan for Medicines for Human Use. Issue 11 (21st September 2020) - Santoro, Aniello; Caplanusi, Irina; Sweeney, Fergus; Cappelli, Benedicte; Nolan, Lorraine; Straus, Sabine; Arlett, Peter
Abstract: Purpose: The article provides an overview of the European Union Incident Management plan (EU‐IMP) and reviews its first 10 years of operation. It outlines its scope, objectives, triggers, principles, and components. Methods: Records were extracted from the European Pharmacovigilance Issues Tracking Tool and a separate tracking system for the period August 20, 2009 to August 19, 2019. Results: During the 10 years of observation, 78 incidents were reviewed by the Incident Review Network and addressed through routine measures. Their number has varied throughout the years with a significant decrease after 2012. Incidents mainly covered safety (56%) and quality (34%) issues or a combination thereof (5%). The majority (70%) were notified by EU regulators and involved centrally and nationally authorized product in similar proportions. A referral was recommended as the assessment pathway for 47% of the issues while lines‐to‐take were the most frequent communication measure (the sole measure in 65% cases). Forty‐six per cent of the issues resulted in a variation, whereas 22% resulted in maintenance of the marketing authorization. Conclusion: The EU‐IMP is underpinned by a robust regulatory framework with defined processes and clear roles and responsibilities and offers a platform to coordinate actions and communication at EU level, rapidly pool expertise, minimize duplications, and address public health incidents.